O Antigo povoamento da herdade do Esporão e das áreas conexas, num raio de 5 km da Torre Medieval - Rocha, Leonor Maria Pereira (2017)
O Antigo povoamento da herdade do Esporão e das áreas conexas, num raio de 5 km da Torre Medieval